2021
DOI: 10.1371/journal.pone.0247902
|View full text |Cite
|
Sign up to set email alerts
|

Symptom Checklist-90-Revised: A structural examination in relation to family functioning

Abstract: The accurate assessment of psychopathological behaviours of adolescents and young adults is imperative. Symptom Checklist-90-Revised (SCL-90-R) is one of the most comprehensive and widely used scales addressing this purpose internationally. Interestingly, associations between the different SCL-90 symptoms and family functioning have been highlighted. Nevertheless, the scale’s factorial structure has often been challenged. To contribute in this area, this study scrutinizes the psychopathological dimensions of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 72 publications
0
10
0
Order By: Relevance
“…To assess anxiety, the State Trait Anxiety Inventory-State (STAI-S) ( 36 ), HADS, POMS, and the Revised Symptom-Checklist-90 (SCL-90-r) ( 37 ) were used in 9 studies involving 1,532 patients. The results of subgroup analyses of the four groups showed statistical significance, and the total results also showed that intervention group had a better improvement in anxiety control than the control group [SMD, −1.36; 95% CI: (−2.13, −0.60); P=0.0005; random-effects model], with significant heterogeneity between subgroups (I 2 =98%, P<0.00001) ( Figure 6 ).…”
Section: Resultsmentioning
confidence: 99%
“…To assess anxiety, the State Trait Anxiety Inventory-State (STAI-S) ( 36 ), HADS, POMS, and the Revised Symptom-Checklist-90 (SCL-90-r) ( 37 ) were used in 9 studies involving 1,532 patients. The results of subgroup analyses of the four groups showed statistical significance, and the total results also showed that intervention group had a better improvement in anxiety control than the control group [SMD, −1.36; 95% CI: (−2.13, −0.60); P=0.0005; random-effects model], with significant heterogeneity between subgroups (I 2 =98%, P<0.00001) ( Figure 6 ).…”
Section: Resultsmentioning
confidence: 99%
“…First, IRT models were estimated with IRT-PRO (Cai et al, 2011 ). Model fit was concurrently determined by: (i) traditional fit indices ( χ 2Loglikelihood ); (ii) marginal likelihood information statistics M 2 (one and two-way marginal tables to correct for potentially sparse information); (iii) RMSEA (< 0.06 = sufficient fit; Hu & Bentler, 1999 ; Gomez et al, 2021a ); and (iv) estimation of error prediction based on Akaike information criterion (AIC; Akaike, 1974 ) and Bayesian information criterion (BIC; Schwarz, 1978 ). Given the potential sensitivity of M 2 to large samples ( N > 900), emphasis was placed on RMSEA to assess model fit (De Ayala, 2008 ).…”
Section: Methodsmentioning
confidence: 99%
“…For example, Olsen et al [ 27 ] reported that the SCL-90 Psychoticism subscale was problematic in a Danish sample, while Prunas et al [ 28 ] opted for an 8-component solution and showed that the eight dimensions partially recombined the items into conceptually coherent domains, such as relational distress or general dysphoria. In clinical samples, the expected factor structure was replicated neither, and the SCL-90 questionnaire was recommended more as a screening instrument for general distress to be supplemented by other diagnostic instruments [ 29 , but see 30 ].…”
Section: Introductionmentioning
confidence: 99%